A comparative usability study using Hierarchical Agglomerative and K-means clustering on Mobile Augmented reality interaction data - Lim K.C.; Selamat A.; Mohamed Zabil M.H.; Yusoff Y.; Selamat M.H.; Alias R.A.; Puteh F.; Mohamed F.; Krejcar O. (IOS Press, 2023)
Augmented reality; Hierarchical clustering; Learning systems; Machine learning; Usability engineering; Hierarchical agglomerative clustering; K-means; Performance metrics; Self-reported metrics; Usability; K-means clustering